A qualitative study exploring stakeholders’ perceptions of registry-based randomised controlled trials capacity and capability in Australia - Bill Karanatsios; Khic-Houy Prang; Justin M. Yeung; Peter Gibbs (Trials)
Abstract Background Traditional randomised controlled trials (RCTs) are the gold standard for evaluating the effectiveness of interventions in clinical research. Traditional RCTs however are complex, expensive and have low external validity. Registry-based randomised controlled trials (RRCTs) are an emerging alternative approach that integrates the internal validity of a traditional RCT with the external validity of a clinical registry by recruiting more real-world patients and leveraging an existing registry platform for data collection. As RRCTs are a novel research design, there is limited understanding of the RRCT landscape in Australia. This qualitative study aims to explore the RRCT landscape in Australia including current capacity and capabilities, and to identify challenges and opportunities for conducting RRCTs. Methods We conducted 30 semi-structured interviews with 18 clinician researchers, 6 research program managers and 6 research governance officers. Interviews were audio-recorded and transcribed verbatim. We analysed the data using thematic analysis. Results We identified four overarching themes: (1) understanding of the RRCT methodology concept and knowledge of Australian clinical registries and RRCT landscape; (2) enablers and barriers in the uptake and conduct of RRCTs; (3) ethics and governance requirements impacting the conduct of RRCTs and (4) recommendations for the promotion, support and implementation of RRCTs. Understanding of and ability to define an RRCT varied considerably amongst participants, as did their appreciation of the role the registry should play in supporting these trials. Lack of ongoing funding to support both registries and RRCTs, along with low awareness and minimal education around this methodology, were identified as the predominant barriers to the uptake of RRCTs in Australia. The simplicity of RRCTs, specifically their pragmatic nature and lower costs, was identified as one of their best attributes. There was consensus that inadequate funding, onerous research governance requirements and poor awareness of this methodology were currently prohibitive in enticing clinicians and researchers to conduct RRCTs. Recommendations to improve the uptake of RRCTs included establishing a sustainable funding model for both registries and RRCTs, harmonising governance requirements across jurisdictions and increasing awareness of RRCTs through education initiatives. Conclusions RRCTs in Australia are an evolving methodology with slow but steady uptake across a number of clinical disciplines. Whilst RRCTs are increasingly identified as a beneficial alternative methodology to evaluate and improve current standards of care, several barriers to effective RRCT implementation were identified. Creating greater awareness of the benefits of RRCTs across a number of stakeholders to help secure ongoing funding and addressing both registry and RRCT governance challenges are two essential steps in enhancing the uptake of RRCTs in Australia and internationally.